2018
DOI: 10.4103/0366-6999.231524
|View full text |Cite
|
Sign up to set email alerts
|

Role of Combining Peripheral with Sublingual Perfusion on Evaluating Microcirculation and Predicting Prognosis in Patients with Septic Shock

Abstract: Background:Measurement of general microcirculation remains difficult in septic shock patients. The peripheral perfusion index (PI) and sublingual microcirculation monitoring are thought to be possible methods. This study was performed to determine whether assessing microcirculation by PI and a new parameter, proportion of perfusion vessel change rate (ΔPPV) from sublingual microcirculation monitoring, can be associated with patients' outcome.Methods:A prospective observational study was carried out, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…However, there remains to be a lack of effective monitoring and early warning when sepsis is early or has not occurred. Sublingual microcirculation monitoring in sepsis patients is used to predict risk stratification and evaluate prognosis, and may guide individualized sepsis treatment in the near future 24,[26][27][28][29] The application of Sidestream Dark Field and Incident Dark Field imaging techniques to analyze sublingual microcirculation and evaluate the degree of microcirculation lesions has been useful. 24 To date, most research on sublingual microcirculation in patients with confirmed sepsis focuses on the relevant treatment and prognosis analysis; research on the changes of sublingual microcirculation before sepsis is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, there remains to be a lack of effective monitoring and early warning when sepsis is early or has not occurred. Sublingual microcirculation monitoring in sepsis patients is used to predict risk stratification and evaluate prognosis, and may guide individualized sepsis treatment in the near future 24,[26][27][28][29] The application of Sidestream Dark Field and Incident Dark Field imaging techniques to analyze sublingual microcirculation and evaluate the degree of microcirculation lesions has been useful. 24 To date, most research on sublingual microcirculation in patients with confirmed sepsis focuses on the relevant treatment and prognosis analysis; research on the changes of sublingual microcirculation before sepsis is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…9 PI has been shown to reflect changes in peripheral circulation perfusion and central hypovolemia, both of which are derived from photoelectric plethysmographic pulse oximetry signals. 10 Some studies have shown that PI can be used as a predictor of early adverse respiratory neonatal outcomes after elective cesarean delivery. 11 It has been suggested to be a reliable and early indicator of regional block success and is known to increase because of the effects of the autonomic blockade during spinal anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…12 In patients with septic shock, PI is related to 6 h lactate clearance. 10 Some studies have used an abnormal PI of <1.4 as a potential trigger to start treatment. In our study, we found that the cutoff value of the PI was <0.6 for predicting ICU mortality in patients with septic shock, resulting in a sensitivity of 77.1% and a specificity of 80%.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies demonstrated that the correction of the Macro did not restore the Micro in septic shock patients after early goal-directed resuscitation. [8,2124] The disordered tissue perfusion is to some extent independent of global circulation in sepsis.…”
Section: Loss Of Resuscitation Coherence In Circulatory Shockmentioning
confidence: 99%